Studies on development of larynx in human newborns and infants - Krawczyński, Marian (Anthropological Review, 1980)
The present author has measured a set of linear dimensions of larynx as well as its volume in 95 newborns and infants. The linear dimensions measured were (see fig. 1): total height of larynx, transversal and sagittal diameter of larynx, height of the frontal wall of larynx, height of the posterior wall, length and width of the aditus, external and internal sagittal dimension of the lower rim of larynx, external and internal oblique dimension of the lower rim, length of glottis (intermembraneous and intercartilagineous part). All measurements were statistically elaborated and relations of larynx dimensions to age, sex and body length of subjects studied (see tables 1 - 8). Results obtained in this study show that volume of the larynx increases already in the newborn phase of life. During infancy growth occurs with respect to: length, width and volume of the larynx. The fastest growth is observed between fourth and eighth month of age. There exists a close correlation between volume of the larynx and age and body length of newborns. Similarly close relationship has been found for age and body length of infants and following characters of the arynx: volume, height, glottis length. These relations can be described by equations of linear regression. Difference between dimensions of larynx in newborns and infants is statistically significant. Sexual dimorphism is present in many characteristics of infants’ larynges. Results obtained with respect to laryngeal dimensions might be treated as an attempt at establishing norms for clinical use.